Towards a new civic bureaucracy : lessons from sustainable development for the crisis of governance - Quinn, Matthew J. (Policy Press, 2022)
Matthew Quinn plots a landmark reimagination of governance and public administration, underpinned by sustainable development and civic republicanism.